Polarization control by Terahertz metamaterials - Cong, Longqing (2017)
Terahertz wave has emerged to be an extremely useful and important tool for applications in sensing, security check and space communications, however, the development is limited due to the weak interaction with the natural occurring materials. The artificially engineered metamaterials are able to provide an excellent platform to manipulate terahertz radiation. Among all the properties of light, polarization is one of the most important characterizations together with its intensity and wavelength. In this thesis, I will focus on the manipulation of polarization state of terahertz radiation using metamaterials from the aspect of applications as real polarizing devices. With the design freedom and the extraordinary optical properties of metamaterials, I discussed the intrinsic symmetry dependence in the unit cell and coupling mechanism in the array for the high-efficiency and broadband operation; and proposed an achromatic terahertz quarter wave plate and an active polarizing device using MEMS technique.